The Risks of "Getting High" on Over-the-Counter Drugs during Pregnancy - Bianca-Eugenia Ősz; Ruxandra Ștefănescu; Andreea Sălcudean; George Jîtcă; Camil-Eugen Vari (MDPI AG, 2024)
Easy access to over-the-counter (OTC) drugs makes it possible to procure active substances that normally used in therapeutic doses do not raise health problems. The use of high doses of OTC drugs containing codeine, loperamide, pseudoephedrine, diphenhydramine or dimenhydrinate, as well as the use of benzidamine systemically raises concerns regarding the increase in units sold. These drugs are used for recreational or euphorizing purposes, including by young women of childbearing age, psychoactive substance users representing a risk group in terms of the possibility of an unplanned pregnancy. Abusive consumption of OTC products during pregnancy is harmful, with consequences for both fetal and late development that can occur in the infant. This literature review presents the risks (teratogenicity, fetal toxicity, neonatal abstinence syndrome, etc.) associated with the use of potentially psychoactive OTC drugs to emphasize the importance of re-evaluating OTC classification and dispensing.